2015
DOI: 10.6061/clinics/2015(02)05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pre- and post-levothyroxine high-sensitivity c-reactive protein and fetuin-a levels in subclinical hypothyroidism

Abstract: OBJECTIVE:The objective of this trial was to determine the levels of inflammatory markers, high-sensitivity C-reactive protein and fetuin-A pre- and post-levothyroxine treatment in cases of subclinical hypothyroidism.MATERIALS AND METHODS:A total of 32 patients with a diagnosis of subclinical hypothyroidism and a control group of 30 healthy individuals were tested for high-sensitivity C-reactive protein and fetuin-A, followed by the administration of 50 µg of levothyroxine in the patient group for 3 months. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
3
34
1
Order By: Relevance
“…CRP levels are correlated with the level of inflammation, and its concentration level is not affected by factors such as age, sex, and physical condition [16]. CRP levels can activate the complement and enhance phagocytosis, thus clearing the pathogenic microorganisms invading the body.…”
Section: Discussionmentioning
confidence: 99%
“…CRP levels are correlated with the level of inflammation, and its concentration level is not affected by factors such as age, sex, and physical condition [16]. CRP levels can activate the complement and enhance phagocytosis, thus clearing the pathogenic microorganisms invading the body.…”
Section: Discussionmentioning
confidence: 99%
“…Christ-Crain et al [ 27 ] first reported increased CRP in patients with OH or SCH citing it as an additional risk factor for development of coronary heart disease in those patients, but further studies have shown conflicting results. Some studies have detected elevated CRP in individuals with hypothyroidism [ 5 , 19 , 24 26 , 29 , 37 39 ], while others have not [ 30 , 40 , 41 ]. Regarding the effect of LRT on CRP, in the current study, in accordance with the first report of Christ-Crain et al [ 27 ] and others [ 30 , 31 , 37 , 39 , 41 ], the CRP level was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have detected elevated CRP in individuals with hypothyroidism [ 5 , 19 , 24 26 , 29 , 37 39 ], while others have not [ 30 , 40 , 41 ]. Regarding the effect of LRT on CRP, in the current study, in accordance with the first report of Christ-Crain et al [ 27 ] and others [ 30 , 31 , 37 , 39 , 41 ], the CRP level was unaffected. However, other studies have shown that normalization of thyroid state by LRT seems to effectively reduce serum CRP [ 19 , 29 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, this is an important index for the diagnosis and assessment of severe pulmonary infectious diseases 47,48 . In the early stage of COVID-19, CRP levels could reflect lung lesions and disease severity 49 as such levels correlate with the level of inflammation 46 . Herein we detected a significant reduction in CRP in patients after two administrations of HeberFERON (see figure 3).…”
Section: Discussionmentioning
confidence: 99%